THE ROLE OF EMPLOYEE MOTIVATION IN ENSURING EFFECTIVE MANAGEMENT OF A COMPANY IN A TURBULENT SOCIO-ECONOMIC ENVIRONMENT - TEPLIUK, Mariia; ANDRIKEVYCH, Victoria (Herald of Khmelnytskyi National University. Economic sciences, 2023)
This article discusses employee motivation as a key factor in ensuring successful business activity. It is proven that employee motivation is an important element of enterprise management and that by increasing its effectiveness, the profitability of the company increases. The opinions of scientists regarding their statements that only motivated personnel can ensure the completion of assigned tasks have been analyzed. At the same time, it is noted that the process of enterprise management through increasing the level of employee motivation should be systematic and take into account the evaluation of employee needs and the observance of values. The most effective motivation lies in the combination of several factors, such as well-paid work, the opportunity for career growth, interesting work, respect from management and colleagues, as well as the possibility of self-realization. Each of these factors is important for creating a motivational environment in the enterprise. The peculiarities of motivating employees under current conditions and why motivation occupies a key position in the company have also been considered. When an organization provides its enterprise with labor resources, uses them rationally, and maintains a high level of labor productivity, this contributes to the effective functioning of the company and ensures a high level of competitiveness. Personnel are the driving force behind any enterprise, so a lot of attention should be paid to such a resource, correctly establishing contacts and various mechanisms for stimulating work. This will be one of the key factors in the success of the company. As for our country - Ukraine, we have a powerful labor potential, but most companies do not use it correctly, which leads to high staff turnover, reducing the attractiveness of companies and, most importantly, their effectiveness and productivity. The opinions of various authors regarding motivation have been considered in this article. Therefore, this article discusses proper work motivation and foreign experience in this matter.
Keywords: motivation; personnel; competitiveness; motivational mechanisms; efficiency